The Assessment Of Pragmatics Competence By English As A Foreign Language Learners At Department Of English Literature - Ridwan Eko Prasetyo Lewenussa; Margaretha Febriany Narahawarin (STKIP Harapan Bima, 2021)
This research focuses on the objectives of 1) the value of pragmatic competence between male and female EFL learners, and 2) the value of pragmatic competence between Papuan and non-Papuan EFL learners in the Department of English Literature. The method used in this research is quantitative. The instrument used in data collection was the Multiple-choice Discourse Completion Test (MDCT) from Birjandi Rezaei (2010). The questionnaire consists of 20 question items and 3 choice options. Questionnaires were distributed to 28 respondents via Google Forms and paper sheets. The received questionnaire data were then assessed and grouped according to the objectives to be sought, namely gender and race. After that, it was analyzed using Microsoft Excel to find the average value. The results of this research were: 1) the pragmatic competence scores of female EFL learners were better than male EFL learners, but the comparison was not too significant. Male EFL students scored well on apologies, while female EFL students scored well on requests. 2) The value of the pragmatic competence of EFL learners between Papuans and non-Papuans is not very significant and is dominated by non-Papuan learners. Papuan EFL learners have a good apology score, while non-Papuan EFL learners have a good request score. As a result, it can be concluded that the pragmatic competence of EFL learners, both gender and race, at the Department of English Literature, is able to use pragmatic competence properly.